Enhancing teaching performance through the adaptation of writing tasks in the official textbook for second Baccalaureate Learners at "Nueve de Octubre" secondary school. - González Sarmiento, Margarita Mariuxi (2018)
The purpose of this research was to investigate the teaching performance of English educators at “Nueve de Octubre” Secondary School regarding the usage of the official textbook when teaching writing to Second Baccalaureate learners. Likewise, this study aimed to evaluate the content and textbook approach that guide the development of writing skills in order to adapt the EFL instruction effectively. This study was conducted through action research. Thus, the first part starts with a literature revision, which provides findings about the Nature of Writing, Writing Approaches, and Principles for Teaching Writing. Furthermore, aspects such as Teacher Professional Development and Effective Strategies for Improving Writing Skills are mentioned. Moreover, relevant facts about how to create an environment conducive for EFL Writers, the role of the teacher when teaching writing in the Ecuadorian curriculum, advantages and disadvantages of using textbooks, and writing tasks in the English textbook B1.1 Student’s Book are also mentioned. The data for this study were collected through questionnaires, surveys, and observation checklists. The information was gathered from the textbook of Second Year of Baccalaureate, and from 250 students and 12 teachers of the educational institution above mentioned. Then, the data were analyzed both, quantitatively and qualitatively. After the analysis, it was concluded that the writing tasks developed in class needed improvement. Accordingly, in pursuit of this goal, a proposal was elaborated. It consists on elaborating an accompanying booklet that provides writing activities and tasks based on the local context and the needs of learners, to further hold teachers’ training sessions that induce their reflection and assist them to visualize clear writing objectives.